소아 천식 환자에서 전신 염증 유형에 따른 천식의 특성 - 설인숙; 김윤희; 이희선; 김민정; 한윤기; 박영아; 김경원; 손명현; 김규언 (Allergy asthma & respiratory disease, 2014)
Purpose: Asthma is a chronic airway inflammation. We evaluated whether systemic inflammatory patterns could reflect the nature of airway inflammation. We assessed characteristics of asthma according to systemic inflammatory patterns. Methods: A total of 413 children with asthma were enrolled in the study. Four systemic inflammatory patterns were classified according to eosinophil and neutrophil counts in peripheral blood. Children with neutrophil count≥5,000/μL were defined as the NEUhi group, those with neutrophil count <2,720/μL as the NEUlo group. The intermediate group with neutrophil count between 2,720/μL and 5,000/uL was excluded from the study. Children with eosinophil≥650/μL were defined as the EOShi group, those with eosinophil count<240/μL as the EOSlo group. The remaining patients were excluded from the study. The characteristics of asthma include pulmonary function test results, bronchodilator response, airway hyperresponsiveness, and atopy. Results: The EOShi group had a lower PC20 (provocative concentration of methacholine causing a 20% fall in forced expiratory volume in 1 second [FEV1]), a lower FEV1, and a higher immunoglobulin E level rather than the EOSlo groups, although there were no significant differences between the NEUhi and NEUlo groups. The eosinophil percentages of the induced sputum samples were higher in the EOShi group than the EOSlo group and correlated with blood eosinophil counts. Conclusion: Eosinophilic inflammation was related to characteristics of asthma and sputum eosinophils. However, neutrophilic inflammation reflected neither asthma features, sputum neutrophils, nor eosinophilic inflammation. Further studies on blood neutrophils involving asthma phenotypes in terms of more specific characteristics of asthma should be needed in children. KCI Citation Count: 0